FOCUSING THE COURT COACHES: A TEACHING/TRAINING STYLE ESSAY (Fiep Bulletin - online, 2014)
To understand the coach's behavior and its style of teaching and training can help the apprehension of its work magnitude. The coach attitudes are, generally, consequences of its education and choices previously made. The following study aims to investigate the conduct and the teaching/training style of court coaches, characterized as a multicase research, with an exploratory descriptive aspect. A semi structured interview was made with four coaches (basketball, futsal, handball and volleyball), a questionnaire was applied and several training days were filmed. To protect the coaches' identity, names of Portuguese Language famous writers were used. The results showed that, three of four coaches are graduated and one of them had a special permission to teach, and they all chose this career motivated by their attendance as athletes on the respective areas; all of them worked as coaches before graduating and to control the training sessions they use, most of all, the personal feeling. Moreover, they expose different teaching concepts. On the productivity dimension, the feedback actions are emphasized, as the proper use of the material, of the space and training time, besides the organization training strategies to its efficacy. On the humanistic dimension, the strong characteristics of positive values formation are highlighted, as the worry about the respect. The worry about the result - the training biggest premise - as long as the formation of individuals with ethic and humanistic values are evident. Despite their idiosyncrasies, the observed coaches successfully followed the theoretical rules about training.
Keywords: coaches; style and conduct; court sports